Healthcare Burden and Productivity Loss Due to Narcolepsy in Sweden - Anna Giertz; Johan Mesterton; Tanja Jakobsson; Stephen Crawford; Somraj Ghosh; Anne-Marie Landtblom (Clocks & Sleep)
Background: Narcolepsy impacts both patients and society, yet there is limited data on its socioeconomic consequences. Methods: This retrospective longitudinal cohort study used pseudonymized patient-level data from Swedish registers and included narcolepsy patients from January 2015–December 2019 and age–sex matched controls. All patients received an index date corresponding to their first narcolepsy diagnosis. Results: This study included 466 incident narcolepsy patients and 2330 matched controls. During the years studied, healthcare resource utilization was 2–5 times higher for incident narcolepsy patients compared to matched controls (p < 0.0001). Modafinil, stimulants, and antidepressants were prescribed more often to incident narcolepsy patients (p < 0.0001). Work productivity was significantly impacted, as incident narcolepsy patients took 7.0–10.5 more sick leave days than their matched controls (p < 0.0001) and had an average of 14.8 net days of disability leave (associated with indirect costs of EUR 1630) versus only 5.8 days among matched controls (EUR 638) during the year of the index (p = 0.027). After controlling for age, sex, and the Charlson comorbidity index, the odds of disability leave were 3.3 times higher in incident narcolepsy patients. Conclusions: This study provides evidence of the magnitude of the substantial societal economic burden due to narcolepsy in Sweden, evidenced by higher healthcare resource utilization and indirect costs.